Method of determining AIS/MAIS trauma scores from ICD 10 diagnosis codes - Kukić Dragoslav; Anđelić Slađana; Marković Marija; Štrbac Mirjana; Rajčević Smiljana; Čolaković Goran (Halo 194)
In 2013, a group of European Union (EU) high representatives for traffic safety published a new definition for severe trauma caused by traffic accidents. According to this definition, severe trauma in road traffic accidents are non-fatal injuries with a Maximum Abbreviated Injury Scale (MAIS) of 3 and above. Therefore, since 2014, the EU has recommended using the Abbreviated Injury Scale (AIS) to assess injuries in traffic accidents and MAIS 3+ to assess severe injuries. Previous experiences in countries that record injuries based on the MAIS 3+ classification system have shown the collected data's high validity and reliability, the reduced risk of making arbitrary conclusions and injury severity subjective assessments, and the reduced risk of inadequate reporting. The MAIS 3+ enables better and more complete data collection on traffic accidents at the national and international levels, the international comparability of data, and the creation of adequate preventive strategies. The upcoming goal is for all EU member states to collect data on severe trauma in traffic accidents based on this definition.